Child Nurture and Learning Assistance for Children in The Family During the Covid -19 Pandemic - Puji Yanti Fauziah; Rita Eka Izzaty; Erma Kusumawardani (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to find out the problems faced by child nurture and learning assistance for children in the family during the covid -19 pandemic. This research is a descriptive qualitative study with a survey method. This research was conducted in Yogyakarta Province. The respondents of this study were parents, totaling 78 people.This study used a closed questionnaire. The results of the study are that the Covid 19 pandemic has made parents experience various obstacles related to parenting and assisting children in learning, ranging from the inability of parents to explain school material, disciplining children, spending too much time with gadgets and technical obstacles faced by 50% of families. These technical constraints are related to signal, wifi, quota and the ability to own gadgets. So that in providing assistance such as quotas, it would be better if support was also given to students who do not have gadgets and assistance for areas that are still having problems with signals because there are no transmitters.